2015
DOI: 10.4028/www.scientific.net/kem.650.38
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficient Sustainable Building Materials: An Overview

Abstract: With the rapid development and modernisation, cities are growing at a very fast pace and the buildings are the main component of cities. Building construction in the world annually consumes around 25% of the global wood harvest, 40% of stone, sand and gravel and 16% of water. It generates 50% of global output of GHG and agents of acid rains. The manufacturing process of building material contributes to Green House Gases such as CO2 to the atmosphere to a great extent. The natural disasters like global warming,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Currently developed new technologies for producing asphalt concrete make it possible to obtain asphalt concrete with higher performance, but they imply the use of expensive polymer or composite materials, new technological equipment, expensive raw materials in the compositions and are not always feasible due to the climatic features of the construction area. [1][2][3][4][5][6][7] This leads to a significant rise in the cost of road construction. Premature destruction of asphalt concrete (wear, destruction of the surface layer of the road surface) can be caused by the aging of bitumen, which is associated with a change in the physical and chemical properties of bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…Currently developed new technologies for producing asphalt concrete make it possible to obtain asphalt concrete with higher performance, but they imply the use of expensive polymer or composite materials, new technological equipment, expensive raw materials in the compositions and are not always feasible due to the climatic features of the construction area. [1][2][3][4][5][6][7] This leads to a significant rise in the cost of road construction. Premature destruction of asphalt concrete (wear, destruction of the surface layer of the road surface) can be caused by the aging of bitumen, which is associated with a change in the physical and chemical properties of bitumen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, designers design, construct, maintain, rehabilitate, and demolish sustainable buildings through the efficient use of natural resources and protecting global ecosystems. The selection of suitable building materials helps to use energy efficiently [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have highlighted the need to achieve energy efficiency at every stage of the life cycle of a building . [ 6 ] Many experiments have studied the possibility of using new materials and technologies in future constructions; such work has investigated energy and resource efficiency, water conservation, improving indoor air quality, and reducing costs [7]. Studies have indicated that the use of natural building materials and building materials derived from recycling processes can save about 50% of energy during the life cycle of a building [8].…”
Section: Introductionmentioning
confidence: 99%